ForceTracker representative contractile graphs. - José M. Rivera-Arbeláez (12418512) (2025)
(A-D) Ribeiro et al.’s platform. (A) Tissue displacement over time. (B) FoC over time. (C) Force per surface area over time. (D) Time of contraction to reach 10% and 90% of the upstroke and downstroke of the contraction cycle. (E-H) Dostanic et al.’s platform. (E) Tissue displacement over time. (F) FoC over time. (G) Force per surface area over time. (H) Time of contraction to reach 10% and 90% of the upstroke and downstroke of the contraction cycle. Representative spontaneous contractions of the tissues shown for both platforms. (TIF)